UJI EFEKTIFITAS EKSTRAK SIWAK (Salvadora Persica) BERBAGAI KONSENTRASI TERHADAP PEMBENTUKAN PLAK GIGI - Studi terhadap Murid MTsN Sale - Ervina Diah Ruslinawati; Rahmawati Sri Praptiningsih; Siti Chumaeroh (Faculty of Dentistry, Universitas Islam Sultan Agung, 2014)
Background: Nowdays many people who care about the health switching from chemical drugs to herbal medicine. There are many herbs that used for health. One is miswak (Salvadora persica) are many benefits to general health and dental health. Siwak can help inhibit dental plaque. Research purposes to determine effectiveness miswak extract against plaque formation. Method: The research was conducted 35 students of Madrasah Tsanawiyah Sale. The samples were divided into five groups, each group of 7 people to extract Siwak 25%, 50%, 75%, 100% and chlorheksidin group. Measurement of plaque index measurement using PHP Plaque Index (Patient Hygiene Performance Index) according Podshadley and Haley. Result: The criteria of dental plaque before rinsing dominant medium, with an average index plaque before rinsing 1,833 chlorheksidin group; 2.119 miswak extract 25%, 2,833 miswak extract 50%; 1,595 miswak extract 75%, and 2,905 miswak extract 100%. The criteria dominant plaque index after rinsing well, with an average index plaque after rinsing 1,476 chlorheksidin group; 1,286 miswak extract 25%; 0,929 miswak extract 50%; 0.690 miswak extract 75%, and 1,310 miswak extract 100%. P value of the one way ANOVA test after rinsing plaque index = 0.018 (p <0.05), means that the average index of dental plaque after rinsing significantly different. Post hoc test results showed 50% miswak extract group and 100% higher than chlorheksidin group, and 25% miswak extract and 75%. Conclusion: Concluded that miswak extract effective against dental plaque formation inhibition. Because the content of trimethylamine (TMA) has miswak which prevents sediment (deposit) particles on the surface of teeth.